Proses Penemuan Makna Hidup Pada Orang yang Menjalankan Mori Tari Mori Uknu - Jil Eltha Sopaheluwakan; Maria Goretti Adiyanti; Enjang Wahyuningrum (Kuras Institute, 2026)
Research on the meaning of life has been studied in an individual context, but there are still limited ones that explore the process of discovering the meaning of life in the context of local cultures that live communally, so this study aims to determine the process of discovering the meaning of life in people who practice Mori Tari Mori Uknu which is a local cultural kinship system that regulates the way of life in relationships with others. Data were collected using a qualitative phenomenological method through interviews and observations. Participants consisted of 5 people with an age range of 24-63 years. They are descendants of Negeri Waru, who also live in Negeri Waru, Central Maluku Regency, who practice Mori Tari Mori Uknu. To ensure the credibility of the data, a source triangulation method was used. The results of the study show that the meaning of life is discovered through several stages, namely (1) receiving and processing information originating from internal and external factors; (2) forming a will to live meaningfully, and (3) being realized in the practice of Mori Tari Mori Uknu, the implementation of which (4) produces positive and negative experiences. From these experiences (5), a source of meaning in life emerges, consisting of values, experiences, attitudes, and creativity. The findings of this study imply that local culture not only functions as a social tradition but also as a psychological framework that facilitates individuals in finding the meaning of life through devotion, self-reflection, and meaningful social relationships, as well as a guideline for directing behavior, ways of thinking, and social relations in society.